Subcontracting sterile pediatric and adult chemotherapy preparations activity: A global risk analysis. Issue 4 (20th June 2022) - Rousseau, Julia; Zribi, Kaouther; Cotteret, Camille; Marcais, Ambroise; Winter, Sarah; Salguero‐Hernandez, Gabriel; Cisternino, Salvatore; Schlatter, Joël
Abstract: Objective: The main purpose of this study was to carry out a global risk analysis (GRA) on the subcontracting circuit to determine and evaluate the risks linked to the future subcontracting process and to propose corrective actions for the most critical risks to ensure safety. This study must allow to conclude in an objective way to the feasibility or not of this project. Methods: A GRA was performed, conducted by a multidisciplinary working group that met in 20 meetings, corresponding to about 50 h of work. Results: We identified 92 scenarios: 13% of scenarios had an initial criticality C1, 40% C2, and 47% C3. The GRA shows that the riskiest scenarios concern the management, material, and equipment with IT system and logistics with transport. The working group identified 25 corrective actions. After implementing those actions, 85% of scenarios had residual criticality C1, 8.5% C2, and 6.5% had residual criticality C3. The working group chose that it was impossible to subcontract part of the activity. Conclusion: The GRA conducted in this study highlighted the risks related to outsourcing this activity, evaluated and prioritized them, and recommended corrective actions. Therefore, we conclude that subcontracting the totality of sterile preparations would be harmful to patient care quality and reactivity for vital medical emergencies, such as macrophage activation syndrome, preparation of clinical trials, graft rejection therapies, preparation of very short stability chemotherapy, and the pediatric graft conditioning chemotherapy.